Dose-dependent effects on cell proliferation, seminiferous tubules, and male germ cells in the fetal rat testis following exposure to di (n-butyl) phthalate - Boekelheide, Kim (2009)
Adult male rats gestationally exposed to di(n-butyl)phthalate (DBP) have dysgenetic testes characterized by seminiferous epithelial degeneration, clustering of Leydig cells, and decreased spermatogenesis. Cell proliferation and apoptosis are key processes regulating development of the testis, and alterations in these processes may underlie testicular dysgenesis. OBJECTIVE: to determine whether gestational exposure to DBP affects cell proliferation and apoptosis in the developing rat testis. Design: pregnant dams were exposed to different dose levels of DBP in mid-gestation and cellular outcomes in fetal and early postnatal testes were assayed by histological and morphometric approaches. RESULTS: gestational exposure to high dose DBP inhibited proliferation of fetal testicular somatic cells but did not affect apoptosis. Exposed fetal testes had a smaller volume and decreased cell numbers, with decreases in both the tubular and interstitial cell populations. A reduction was observed in the testis volume and altered seminiferous tubule morphometry at ≥50 mg/kg/d, and a decreased testicular cell number at ≥30 mg/kg/d DBP. The number of multinucleated gonocytes in DBP-exposed fetal testes increased after exposure to ≥100 mg/kg/d. The number of proliferating cells in the DBP-exposed testis rapidly rose after birth (when exposure stopped), and the testis volume and the total cell number was comparable to control by postnatal day 2. Conclusion: DBP reversibly inhibits proliferation of somatic cells in the fetal rat testis. Decreased proliferation, rather than increased apoptosis, is the underlying mechanism of altered fetal development of DBP-exposed seminiferous tubules contributing to testicular dysgenesis.